FORMATION IN PANTUN OF LANGKAT MALAY TRADITIONAL WEDDING CEREMONY - Dina Finanti; Muhammad Natsir; Rahmad Husein (State University of Medan, 2019)
The purpose of this study was to conduct the formation in Pantun of Langkat Malay traditional wedding ceremony by using Sibarani’s theory. Formation itself is text, co-text, and context which aimed to know the purpose of an oral tradition. The method used in this paper was descriptive and qualitative. For collecting the data the researcher became an instrument by doing observation and unstructured interview. Analysis technique used which were transcribing, reading, comprehending, investigating, describing, and explaining. The findings of text showed theme in Pantun that uttered by telangkai contained gratitude, honor, tradition, persuasion, joke, hoping a kindness, signifying a peace, welcoming guest, enthusiastic, teasing which briefly supported by co-text and context. Co-text described paralinguistic, kinetic, proxemic, and material elements. Some context applied as follow; cultural context, social context, context of situation, and cultural context.Keywords: Text, Co-text, Context, Pantun, Langkat Malay Traditional Wedding Ceremony